ANALISIS TREN TINGKAT PENGANGGURAN TERBUKA DI PROVINSI KEPULAUAN RIAU TAHUN 2015–2024 - Waldy Saragih; Hardian Putra Rumapea; Sri Ningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the trends in the open unemployment rate in the Riau Islands Province during the period 2015–2024 and to identify the factors influencing its changes. The open unemployment rate is an important indicator in assessing labor market conditions and regional economic stability. This study employs a quantitative descriptive method using secondary data obtained from the Central Statistics Agency (BPS). The data analyzed consist of the annual open unemployment rate in the Riau Islands Province over the past ten years.The results show that the open unemployment rate in the Riau Islands fluctuated during the study period, with a significant increase in 2020–2021 due to the impact of the global pandemic, followed by a decline during the economic recovery period after 2022. Factors influencing changes in the unemployment rate include regional economic growth, industrial sector development, investment dynamics, and labor force demographic characteristics.This study is expected to provide an overview of employment conditions in the Riau Islands and serve as a reference for local governments in formulating appropriate policies to reduce unemployment.